Development and Implementation of a Healthcare Database Analysis Course for Graduate Students - David R. Axon (MDPI AG, 2022)
There emerged a need to develop and implement a new healthcare database analysis course for Health Economics and Outcomes Research (HEOR) graduate students, which would allow students to apply their biostatistics and study design skills to answer healthcare-related research questions using large datasets. This communication establishes the need for this course, describes how the course was conceptualized, provides an overview of the course content, course cohort, and course outcomes, and discusses lessons learned from this process. This course was developed to meet the need of HEOR graduates to perform real-world data studies. The course required students to conceptualize a study, apply their data analysis skills to analyze the data, and develop their scientific writing skills by preparing a conference abstract and research report that should be submitted for publication. Lessons learned include focusing more on developing advanced research methodologies and less time on preparing dissemination materials, which can instead be done in subsequent courses or for independent study credit.